Perencanaan Tata Ruang sebagai Upaya Mewujudkan Pembangunan Kota Berkelanjutan (Studi Analisis Rencana Tata Ruang Wilayah Kota Mojokerto) - Adianti, Shelly Yunita (Jurnal Ilmiah Administrasi Publik, 2020)
The social and environmental conditions in Mojokerto city have decreased and marked by several things, namely pollution due to the burden of emissions, not optimal public transport, not optimal management of the informal sector, the conversion of land. This study focuses on assessing the ability of the substance of spatial urban planning in Rencana Tata Ruang Wilayah (RTRW) of Mojokerto city to realize sustainable city development. The concept of a sustainable city is used to identify and criticize the RTRW of Mojokerto city, based on 5E criteria (Economy, Equity, Ecology, Engagement, and Energy). Stakeholders have a lot of influence in the formulation of the substance of spatial urban planning, so 5E criteria for criticizing the RTRW is reviewed through the stakeholders' perspective.